Analysis and evaluation of the performance efficiency of micro-agricultural projects (vegetable status) in Lattakia - مسلم رنيم; إبراهيم صقر; علي أحمد (Latakia University Journal -Biological Sciences Series, 2024)
The research aimed to evaluate the performance efficiency of micro-agricultural projects specialized in vegetable production in Latakia Governorate, in terms of the following dimensions (economic, environmental, social, internal operations, learning and growth) and to identify the most prominent difficulties facing project owners. To achieve the research objectives, a questionnaire form was designed, It was distributed to a random sample of 136 farmers in the areas of Latakia Governorate (Jableh, Al-Haffa, Qardaha, Latakia). Performance efficiency was evaluated using a three-way Likert scale, in addition to applying financial and productivity standards. The results showed a high economic efficiency for micro-vegetable production projects, reaching 2.51, the productivity of the invested capital 2.51 SP, the profitability factor 151.35%, and the recovery period of the invested capital did not exceed 0.66 years. The results also indicated that the most prominent difficulties and obstacles faced by the agricultural projects in the studied sample were the high costs of all raw materials and requirements for the production process, the lack of sufficient irrigation water to irrigate the crops, and the lack of electricity and fuel needed to pump water. The results also highlighted the major role played by agricultural projects. Micro-business (vegetable production) increases individuals’ incomes and improves their standard of living. The research recommended the need to provide support to farmers by securing sufficient water sources to irrigate crops, considering increasing the electrical supply to water pumping stations, and securing access to agricultural grants provided by international organizations, to push farmers to invest in the field of micro-agricultural projects.